2012
DOI: 10.1038/labinvest.2012.67
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines induce tight junction disassembly in airway cells via an EGFR-dependent MAPK/ERK1/2-pathway

Abstract: Epithelial barrier permeability is altered in inflammatory respiratory disorders by a variety of noxious agents through modifications of the epithelial cell structure that possibly involve tight junction (TJ) organization. To evaluate in vitro whether pro-inflammatory cytokines involved in the pathogenesis of respiratory disorders could alter TJ organization and epithelial barrier integrity, and to characterize the signal transduction pathway involved Calu-3 airway epithelial cells were exposed to TNF-a, IL-4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
82
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(91 citation statements)
references
References 50 publications
8
82
1
Order By: Relevance
“…S2A,B). This observation is consistent with earlier findings that the activation of Erk1/2 is involved in the disruption of the epithelial tight junction barrier by downregulating tight junction proteins (Petecchia et al, 2012;Samak et al, 2011). Collectively, these data support the notion that overexpression of wild-type or active rpS6 leads to a downregulation of p-Akt, resulting in the activation of Raf-MER-Erk signaling that upregulates MMP-9.…”
Section: Research Articlesupporting
confidence: 93%
“…S2A,B). This observation is consistent with earlier findings that the activation of Erk1/2 is involved in the disruption of the epithelial tight junction barrier by downregulating tight junction proteins (Petecchia et al, 2012;Samak et al, 2011). Collectively, these data support the notion that overexpression of wild-type or active rpS6 leads to a downregulation of p-Akt, resulting in the activation of Raf-MER-Erk signaling that upregulates MMP-9.…”
Section: Research Articlesupporting
confidence: 93%
“…TNF-␣ activates MAPK and NF-B to induce inflammatory cytokines and chemokines such as IL-8, triggers inflammatory responses, and leads to changes in the expression of TJ-related molecules; for example, it increases MLCK expression and decreases ZO-1 expression through activation of p38 (42)(43)(44)(45). In this study, the pretreatment of HYA normalized the expression of occludin, ZO-1, and MLCK in Caco-2 cells (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…studies from other laboratories have reported that MAPKs might play a role in the disruption of TJs via mediating phosphorylation of TJ proteins in response to external cues in epithelial cells (34,35). Therefore, to investigate the upstream mechanisms of ZO-1 phosphorylation by 15(S)-HETE, we tested the role of MAPKs.…”
Section: Erk1/2 Mediate 15(s)-hete-induced Zo-1 Phosphorylation-previousmentioning
confidence: 99%